(untitled) (ASEAN Engineering Journal, 2012)
The prediction behavior of improved soft soil using vacuum preloading method should be concerned significantly not only in the laboratory but also in the field. It aims at avoiding the risks of instability of the embankment surcharging during construction. The simulation vacuum preloading method using tri-axial apparatus is proposed to predict the behavior of soft soil improvement in the laboratory and the increasing of undrained shear strength of soil specimen at any degree of consolidation. The simulation has been carried out at Hokkaido University, while the undrained shear strengths, at 40%, 70% and 100% of vacuum consolidation are at 43.2kPa, 53.8kPa and 62.49kPa, respectively by tri-axial apparatus. This modeling is the effective method to determine the increasing rate of strength of the ground corresponding to loading rate during consolidation process, and to restrict using field test during construction, the cause of damage of airtight sheet membrane, and lossing of vacuum pressure. A case study of vacuum consolidation on very soft clay at Nakhorn Sri Thammarat Airport project is presented.